DESIGN OF EARTHQUAKE-RESISTANT STRUCTURE BAKAUHENI LAMPUNG FERRY TERMINAL - Yomantara, Jefferson
Java and Sumatera Islands need crossing facility to allow connectivity between the two island. In order to achieve that, a ferry port infrastructure in Bakauheni, Lampung is required. The infrastructure that is designed for the design scope of the port is ferry terminal to facilitate passangers’ departure and arrival. The unique of terminal port design is consist of additional roof structure that able to move, which make the terminal port structure become retractable. The structure of terminal port consist of 2 floors with total height of 20 meters. Using steel as construction material, structure will be design as Dual System which is combination between Intermediate Moment Resisting Frame (IMF) and Special Concentrically Braced Frame (SCBF). After the structural system is determined, analysis using spectral response analysis will be performed. Analysis will include story drift check, p-delta effect, horizontal irregularities, vertical irregularities, dual system and redundancy check. Next, the elements of structure which are frames will be checked to fulfill the requirements of the strength and serviceability of each frame. In this case, the serviceability that will be concerned is deflection limit check. After that, each component of the structure will be detailed (detailing), which include connection design, diaphragm analysis and design, shear stud design, base plate design, pedestal and tie beam design.